The Effect of Okra (Abelmoschus esculentus (L.) Moench) Seed Extract on Human Cancer Cell Lines Delivered in Its Native Form and Loaded in Polymeric Micelles - Chaemsawang, Watcharaphong; Prasongchean, Weerapong; Papadopoulos, Konstantinos I.; Ritthidej, Garnpimol; Sukrong, Suchada; Wattanaarsakit, Phanphen (International Journal of Biomaterials, 2019)
Cancer is a noncommunicable disease with a high worldwide incidence and mortality rate. The National Cancer Institute of Thailand reports increasing cumulative incidence of breast, colorectal, liver, lung, and cervical cancers, accounting for more than 60% of all cancers in the kingdom. In this current work, we attempt to elucidate the phytochemical composition of the okra (Abelmoschus esculentus (L.) Moench) seed extract (OSE) and study its anticancer activity, delivered in its native form as well as in the form of polymeric micelles with enhanced solubility, in three carcinoma cell lines (MCF-7, HeLa, and HepG2). The presence of flavonoid compounds in the OSE was successfully confirmed, and direct delivery had the highest cytotoxic effect on the breast cancer cell line (MCF-7), followed by the hepatocellular carcinoma (HepG2) and cervical carcinoma (HeLa) cell lines in that order, while its delivery in polymeric micelles further increased this effect only in the HepG2 cell line. The OSE’s observed cytotoxic effects on cancer cell lines demonstrated a dose and time-dependent cell proliferation and migration inhibition plausibly due to VEGF production inhibition, leading to apoptosis and cell death, conceivably due to the four flavonoid compounds noted in the current study, one of which was isoquercitrin. However, in view of the latter compound’s isolated effects being inferior to those observed by the OSE, we hypothesize that either isoquercitrin requires the biological synergy of any one or all of the observed flavonoids or any of the three in isolation or all in concert are responsible. Further studies are required to elucidate the nature of the three unknown compounds. Furthermore, as we encountered significant problems in dissolving the okra seed extract and creating the polymeric micelles, further studies are needed to devise a clinically beneficial delivery and targeting system.